Additional file 1 of Prey and habitat distribution are not enough to explain predator habitat selection: addressing intraspecific interactions, behavioural state and time - Alexis Grenier-Potvin (10335840); Jeanne Clermont (4489282); Gilles Gauthier (148776); Dominique Berteaux (124789) (2021)
Additional file 1.